Postharvest treatment of hydrogen sulfide delays the softening of Chilean strawberry fruit by downregulating the expression of key genes involved in pectin catabolism - Molinett, Sebastian A.; Alfaro, Juan F.; Sáez, Felipe A.; Elgueta Palma, Sebastián Andrés.; Moya León, María A.; Figueroa, Carlos R. (MDPI, 2021)
Hydrogen sulfide (H2S) plays several physiological roles in plants. Despite the evidence, the role of H2S on cell wall disassembly and its implications on fleshy fruit firmness remains unknown. In this work, the effect of H2S treatment on the shelf-life, cell wall polymers and cell wall modifying-related gene expression of Chilean strawberry (Fragaria chiloensis) fruit was tested during postharvest storage. The treatment with H2S prolonged the shelf-life of fruit by an effect of optimal dose. Fruit treated with 0.2 mM H2S maintained significantly higher fruit firmness than non-treated fruit, reducing its decay and tripling its shelf-life. Additionally, H2S treatment delays pectin degradation throughout the storage period and significantly downregulated the expression of genes encoding for pectinases, such as polygalacturonase, pectate lyase, and expansin. This evidence suggests that H2S as a gasotransmitter prolongs the post-harvest shelf-life of the fruit and prevents its fast softening rate by a downregulation of the expression of key pectinase genes, which leads to a decreased pectin degradation.
Keywords: Fragaria chiloensis.; Strawberry decay.; Shelf-life.; Call wall disassembly.; Pectinases.; Gasotransmitter.; Gasotransmitters.